Exploring the online reading comprehension strategies used by sixth-grade skilled readers to search for and locate information on the Internet - Julie Coiro (Reading Research Quarterly, 2007)
The purpose of this qualitative study was to explore the nature of reading comprehension processes while reading on the Internet. Eleven sixth-grade students with the highest combination of standardized reading scores, reading report card grades, and Internet reading experiences were selected from a population of 150 sixth graders in three different middle schools in the central and northeastern United States. These 11 skilled readers met individually with a researcher and completed two separate tasks that involved reading within multilayered websites or using the Yahooligans! search engine. Students answered specific questions about their strategy use in a follow-up interview after each reading session. Qualitative analysis evolved through four distinct phases, each of which involved reviewing data from think-aloud protocols, field observations, and semistructured interviews to provide insights on the nature of online reading comprehension. Findings suggested that successful Internet reading experiences appeared to simultaneously require both similar and more complex applications of (1) prior knowledge sources, (2) inferential reasoning strategies, and (3) self-regulated reading processes. The authors suggest that reading Internet text prompts a process of self-directed text construction that may explain the additional complexities of online reading comprehension. Implications for literacy theory and future research are discussed. (Contains 5 tables and 4 figures.)
Keywords: compétences; formation à distance; grade 6; stratégie de lecture; stratégies d'apprentissage